Evaluation of half-sib progenies from CMS-39 maize population under different environmental conditions. - Aguiar, Paulo Antônio de; Ramalho, Magno Antônio Patto; Magnavaca, Ricardo; Andrade, Marco Antônio de (Pesquisa Agropecuaria Brasileira, 2014)
Four hundred halt-sib families, from the CMS-39 maize population were assessed at three localities: Lavras, Ijaci and Sete Lagoas, in the State of Minas Gerais, Brazil, during the agricultural year 1984/85, to verify the breeding potential of this population and the existence of family x environment interaction. The CMS-39 maize population was obtained by the National Research Center for Maize and Sorghum at Sete Lagoas, MG, and was synthesized by recombining 55 cultivars. The experimental design used was a 20 x 20 lattice with two replications and each plot consisted of one row five meters long. The estimates obtained for phenotypic and genotypic parameters, showed that the population is highly variable. The estimated variance for family x environment interaction was high, indicating the need of families to be evaluated in more than one environment. The estimate of the expected gain with selection among families, considering the mean families in three localities, was of 10,28% for ear weight. The partitioning of family x locality interaction showed that it was due mainly to the lack of correlation between the performance of the families in the various localities.